Consciência fonológica e sucesso na aprendizagem da leitura e da escrita: melhor prevenir do que remediar - Carvalho, Lina Maria de Moraes (2010)
Recent developed researches at the area of Cognitive Science of Reading are emphasizing the importance of the metalinguistics skills to promote the success at the initial learning of reading and writing. Programs of pedagogical intervention aim to develop abilities of phonological awareness have shown themselves efficacious to favour the development of these abilities and the learning of reading and writing, including at students with difficulties at this learning. Based on these assumptions and considering the reduced number of these researches in Brazil, specially with students who have difficulties at learning of written language, the present study investigated the effects of a program of intervention - composed by activities and games which aim to develop abilities of phonological awareness - about the learning of reading and writing of children from the 3rd and 4th junior school with difficulties at this learning. The research was done at a public municipal school, in Teresina-Pí. The study involved 18 children both genders distributed in two groups: the experimental group with 9 children aged 7,1 to 9,3 years and the control group with 9 children aged 7,5 to 9,1 years. The research followed the experimental design developed in three phases: pre-test, intervention and pos-test. Tests of phonological awareness, written of words, reading of words and knowledge of letters were used. The written test was applied simultaneously to the children and the others were applied individually by the researcher to each children before and after the intervention. The intervention program is composed by five units of activities and games which aim to develop phonological awareness skills. It was developed by the researcher with the participants of the experimental group, three times a week, in 24 sessions of activities, each one lasts 90 minutes. The data were analyzed and discussed in confront to other results of research in this field. The results showed positive effects of the intervention on the performance of the experimental group, at the abilities of phonological awareness as at the writing and reading of words, supporting the hypothesis of co-relation between the deficit in phonological awareness and difficulties at the acquisition of reading and writing. These results confirm that the programs of instructive activities in phonological awareness are efficacious to develop the phonological awareness and favour the acquisition of reading and writing in students with difficulties at the learning of these abilities. The results give evidences on the importance of explicit and systematic teaching of correspondences between graphemes and phonemes and phonemic awareness at the beginning of school learning, to promote the success at the learning of reading and writing, showing it s better to prevent than to remedy